Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode RGEC (Risk Profile, Good Corporate Goverance, Earnings Dan Capital) - Zahro Hartati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the soundness of state-owned banks for the 2021-2022 period in terms of the aspects of Risk profile, Good Corporate Governance (GCG), Earnings, Capital, and RGEC as a whole. This type of research is a quantitative descriptive research with research subjects in the form of state-owned banks listed on the Indonesia Stock Exchange in 2021-2022. The data was obtained through documentation techniques. The data analysis technique used is the soundness analysis of a bank using a risk approach (Risk-based Bank Rating) with the scope of the assessment covering RGEC factors. The results of the study show that during the 2021-2022 period: (1) The risk profile aspect of BUMN banks is in a healthy condition with an average NPL value of 2.64% and 2.37%, and an LDR of 66.8% and 65.6 % are in very good health. (2) The GCG aspect during the 2021-2022 period is 2% and 1.6% with healthy and very healthy criteria. (3) The Earnings aspect for the 2021-2022 period is in healthy and very healthy condition with an average ROA value of 1.66% and 2.26% and BOPO of 60.8% and 58.64%. (4) The Capital aspect is in very healthy condition with an average CAR value of 19.3% and 18.6%. (5) The RGEC aspect as a whole is in Composite Rating 1, which is very healthy with a score of 87%.